Modern Methods, Techniques of Understanding Reading in High School (Eurasian Research Bulletin, 2022)
Reading in a foreign language in the educational activities of students of language universities traditionally occupies a significant place through reading, the student gets acquainted with various aspects of the life of society and culture of the language being studied, comprehends someone else's mentality, he forms an image of the country, which contributes to his cultural enlightenment.